Research productivity over the life cycle: evidence for academic scientists - Levin, Sharon G.; Stephan, Paula E. (American Economic Review, 1991)
The relationship between age and the publishing productivity of Ph.D. scientists is analyzed using data from the Survey of Doctorate Recipients (National Research Council) and the Science Citation Index. The longitudinal nature of the data allows for the identification of pure aging effects. In five of the six areas studied, life-cycle aging effects are present. Only in particle physics, where scientists often speak of being on a "religious quest, " is the indication that scientific productivity is not investment-motivated. Vintage effects are also considered. The expectation that the latest educated are the most productive is not generally supported by the data. Copyright 1991 by American Economic Association.